SIGNS IDENTIFY AREAS TO INCREASE TECHNICAL LOSS AND UNAUTHORIZED ELECTRICITY CONSUMPTION IN ELECTRIC NETWORKS - Alexander Grin; Anna Grin; Irina Skorokhodova (Вестник Северо-Кавказского федерального университета, 2022)
In article tendencies and problems reduce the efficiency of the distribution grid companies. A methodological approach to identify places in the electrical network based on analysis of information regime increased technical losses of electricity. The criteria to identify sites of unauthorized consumption of electricity on the basis of statistical methods and analysis of load profiles derived from Smart Metering System.